Therapeutic Targeting of Ras/Raf/Mapk Pathway by Natural Products: A Systematic and Mechanistic Approach for Neurodegeneration - Echeverria-Morgado, J (Elsevier GmbH, 2023)
Background: Multiple dysregulated pathways are behind the pathogenesis of neurodegenerative diseases (NDDs); however, the crucial targets are still unknown. Oxidative stress, apoptosis, autophagy, and inflammation are the most dominant pathways that strongly influence neurodegeneration. In this way, targeting the Ras/Raf/mitogen-activated protein kinases (MAPKs) pathway appears to be a developing strategy for combating NDDs like Parkinson s disease, Alzheimer s disease, stroke, aging, and other NDDs. Accordingly, plant secondary metabolites have shown promising potentials for the simultaneous modulation of the Ras/Raf/MAPKs pathway and play an essential role in NDDs. MAPKs include p38 MAPK, extracellular signal-regulated kinase 1/2 (ERK 1/2), and c-Jun N-terminal kinase (JNK), which are important molecular players in neurodegeneration. Ras/Raf, which is located the upstream of MAPK pathway influences the initiation and progression of neurodegeneration and is regulated by natural products. Purpose: Thus, the present study aimed to investigate the neuroprotective roles of plant- and marine-derived secondary metabolites against several NDDs through the modulation of the Ras/Raf/MAPK signaling pathway. Study design and Methods: A systematic and comprehensive review was performed to highlight the modulatory roles of natural products on the Ras/Raf/MAPK signaling pathway in NDDs, according to the PRISMA guideline, using scholarly electronic databases, including PubMed, Scopus, and Web of Sciences. Associated reference lists were also searched for the literature review. Results: From a total of 1495 results, finally 107 articles were included in the present study. The results show that several natural compounds such as alkaloid, phenolic, terpenoids, and nanoformulation were shown to have modulatory effects on the Ras/Raf/MAPKs pathway. Conclusion: Natural products are promising multi-targeted agents with on NDDs through Ras/Raf/MAPKs pathway. Nevertheless, additional and complementary studies are necessary to check its efficacy and potential side effects. © 2023 Elsevier GmbH
Keywords: Neurodegeneration; Ras/Raf/APKs signaling pathway; Natural products; Mechanistic approach